The Future Development and Social Implications of the Metaverse - Liu, Mengyu (Journal of Modern Social Sciences, 2025)
The Metaverse, as an emerging virtual world, is gradually transforming human social relationships and behavior patterns. This paper explores the Metaverse from a social science perspective, examining its technological foundations, impact on social interactions, changes in behavior patterns, governance, and ethical challenges, while also forecasting its future development trends. The study reveals that the decentralized nature, immersive experience, and virtual economy of the Metaverse are shaping new forms of social interaction and raising a series of legal and ethical issues. Finally, this paper proposes governance and policy recommendations for the future development of the Metaverse to ensure its healthy growth.